This is a mock-exam question:

The following measurements have been made

$\hat{\gamma}(0) = 570, \quad \hat{\gamma}(1) = 505, \quad \hat{\gamma}(2) = 460, \quad \hat{\gamma}(3) = 420$

Suppose that the data was generated from an $AR(2)$ model,

$X_t - \phi_1 X_{t-1} - \phi_2 X_{t-2} = Z_t$

where $\{Z_t\} \sim WN(0,\sigma^2)$. Estimate the variance $\sigma^2$.

What i've tried is simply to use the Yule-Walker equations to estimate the variance, \begin{equation*} \gamma(k) - \phi_1 \gamma(k - 1) - ... - \phi_p \gamma(k - p) = \begin{cases} 0, \quad &\text{if } k = 1, ..., p \\ \sigma^2, \quad &\text{if } k = 0 \end{cases} \end{equation*} which, if $k = 0$, should give $\gamma(0) = \hat \gamma(0) = \sigma^2 = 570$. But the answer is $\sigma^2 = 121$.

What am I missing here?


1 Answer 1


$\gamma(0)$ is the variance of $X_t$, it is not in general equal to the variance of $Z_t$, which is what you're looking for.

You may also be misinterpreting the above equation. For $p=2$ and $k=0$, it says that:

$$\gamma(0) - \phi_1 \gamma(-1) - \phi_2 \gamma(-2) = \sigma^2$$

It does not say that $\gamma(0) = \sigma^2$. The terms where $\gamma(i)$ has a negative argument are not implicitly dropped or anything like that. Since $\gamma$ is symmetric, it also says that:

$$\gamma(0) - \phi_1 \gamma(1) - \phi_2 \gamma(2) = \sigma^2$$

You can combine this with the same equation for $k=1$ and $k=2$ to build a linear system with 3 equations and 3 unknowns, something like this:

$$\begin{pmatrix} \gamma(1) && \gamma(2) && 1 \\ \gamma(0) && \gamma(1) && 0 \\ \gamma(1) && \gamma(0) && 0 \end{pmatrix} \begin{pmatrix} \phi_1 \\ \phi_2 \\ \sigma^2 \end{pmatrix} = \begin{pmatrix} \gamma(0) \\ \gamma(1) \\ \gamma(2) \end{pmatrix} $$

More typically this is done in two steps, solving for the $\phi_i$ first in the smaller system:

$$\begin{pmatrix} \gamma(0) && \gamma(1) \\ \gamma(1) && \gamma(0) \\ \end{pmatrix} \begin{pmatrix} \phi_1 \\ \phi_2 \end{pmatrix} = \begin{pmatrix} \gamma(1) \\ \gamma(2) \end{pmatrix} $$

And then plugging in $\phi_i$ into the remaining equation to get $\sigma^2$.

Either way, the result is:

$$\sigma^2 = \left(\gamma(0) - \gamma(2)\right) \left( 1 + \frac{\gamma^2(1)-\gamma(0)\gamma(2)}{\gamma^2(1)-\gamma^2(0)}\right)$$

Substituting for the $\hat{\gamma}(i)$, you'll get to $\hat{\sigma}^2 \approx 121$.

  • $\begingroup$ +1: This is a fantastic answer. It clarified a lot of things for me. I'd give it some extra points if I could. $\endgroup$ Oct 8, 2021 at 11:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge that you have read and understand our privacy policy and code of conduct.

Not the answer you're looking for? Browse other questions tagged or ask your own question.